2016
DOI: 10.1177/0093650215626983
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mindfulness on Empathy, Active Listening, and Perceived Provisions of Emotional Support

Abstract: Mindfulness has emerged as an important factor that assists people in regulating difficult emotions, but it is not yet known whether mindfulness plays a role in supportive communication. The current study examines whether mindfulness facets (describing, observing, nonjudging, aware acting, nonreacting) positively influence self-reported abilities to (a) discern more and less person-centered (PC) supportive messages and (b) facilitate reappraisals via two core cognitive factors, namely, empathy and active liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 109 publications
(153 reference statements)
3
49
0
2
Order By: Relevance
“…As such, the outcomes observed must be regarded as more distal indicators of therapy‐relevant skills. However, findings from other studies have established empirical associations between the variables included here and measures more closely related to the therapy process, such as empathy (Jones et al, ) and maintenance of therapeutic alliance (Leonard et al, ; Razzaque et al, ). It may thus be argued that it is likely that the changes observed here are relevant for the practice of psychotherapy.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…As such, the outcomes observed must be regarded as more distal indicators of therapy‐relevant skills. However, findings from other studies have established empirical associations between the variables included here and measures more closely related to the therapy process, such as empathy (Jones et al, ) and maintenance of therapeutic alliance (Leonard et al, ; Razzaque et al, ). It may thus be argued that it is likely that the changes observed here are relevant for the practice of psychotherapy.…”
Section: Discussionmentioning
confidence: 87%
“…According to Wampold et al (), the ability to modulate and express emotions and maintain focus on the client is a skill that is of importance for therapist effectiveness. Prior research has found facets of mindfulness to be related to therapeutic alliance (Leonard et al, ; Ryan et al, ), as well as to empathy and active listening (Jones, Bodie, & Hughes, ). The benefit of mindfulness training in enhancing various aspects of facilitative interpersonal skills is worthy of further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can have direct positive consequences on behaviour, especially in relation to bullying. For example, mindfulness has been linked to empathy and perspective taking (Jones, Bodie, & Hughes, 2016). Furthermore, empathy has been linked to positive bystander behavior (Barlińska, Szuster, & Winiewski, 2015) which in turn has been linked to reductions in bullying (Polanin, Espelage, & Pigoot, 2012).…”
Section: Considering Mindfulnessmentioning
confidence: 99%
“…These findings support other studies which have similarly shown that higher levels of bonding and attachment between interlocutors correlate with greater interpersonal communication skills (Klaus & Kennell, 1972;Karen, 1998;Levine & Heller, 2010). Condon and Ogston (1966) with the other interlocutor and the speaker will be fully aware that the listener is in fact interested in listening to them (Jones, Bodie, & Hughes, 2016). In summary, demonstrating active listening improves not only the efficiency with which information is exchanged but also has the potential to develop the emotional aspect of the relationship between the interlocutors.…”
Section: Applying Multimodal Listening: Active Listening Across Variomentioning
confidence: 95%